Rebel Together Sebagai Strategi Komunikasi Pemasaran Digital Madformakeup Di Tengah Pandemi COVID-19 - Julianti, Indri; Delliana, Santi (Communicatus: Jurnal Ilmu komunikasi, 2020)
The appearance of virus COVID-19 pandemic has made businesses change their marketing communication strategic ways to survive in this pandemic, including makeup companies like Madformakeup. One of the strategies used by Madfromakeup is planning a fair and effective digital marketing communication strategy and implementing customer engagement through the Rebel Together program. This study aims to determine the digital marketing communication strategy adopted by Madformakeup in increasing sales during the COVID-19 pandemic. The method that the researcher used is a qualitative method with the type of descriptive research. The results of this study are that Madformakeup implemented a digital marketing communication strategy during the COVID-19 pandemic so well and effectively through the STP and IMC concepts. To produce a digital marketing communication strategy that can be accepted by the public, especially customers from Madformakeup. Researchers collected data through interviews, observation, and documentation in the form of photos.